Process, the Constitution, and Substantive Criminal Law - Bilionis, Louis D. (1998)
Criminal law scholars have pined for a substantive constitutional criminal law ever since Henry Hart and Herbert Packer first embraced the notion in the late 1950s and early 1960s. To this day, scholars continue to search for a theory fhat giv:es content to, in Hart's words, the unmistakable indications that the Constitution means something definite and spμiething serious when it speaks of 'crime.' To their dismay, the Supreme Court has - with two exceptions - seemingly resisted the notion. The two exceptions are familiar. First came the 1957 case of Lambert v. California, in which the Court came as close as it ever has to constitutionalizing a mens rea requirement as fundamental to the just imposition of a criminal sanction. Lambert was followed in 1962 by Robinson v. California, in which the Court came as close as it ever has to constitutionalizing criminal law's other Latin half, the element of actus reus. Both cases were certifiable breakthroughs that found previously unrecognized content in the Due Process Clause and the Eighth Amendment, respectively, to limit the power of American legislatures to define criminal laws. Both decisions were tantalizing symbols as well. They held out hope for a vibrant relationship between the Constitution and the criminal law, one that might develop new principles to help bring about a more humane, moral, and altogether more sound substantive penal law